Management and Factors associated with Acute Appendicitis during Pregnancy: Clinical Evaluation and Outcomes - Ismael Atiyah Kurji; Walah Imad Abdulrazzaq (Academic Journal of Clinicians, 2024)
Background: Acute appendicitis (AA) is the commonest non-obstetrical surgical emergency during pregnancy. Diagnosis and management of acute appendicitis (AA) during pregnancy remain important challenges among surgeons in their daily practice. Different factors may contribute to the development of AA, management and outcomes of appendectomy during pregnancy. Objective: To assess, analyze and compare the management practices, associated factors and outcomes of acute appendicitis among Iraqi pregnant women . Methods: This was a cross sectional study with analytic utility included 172 Iraqi women aged between 18 and 35 years who were surgically treated for acute appendicitis. Data collection and patients enrollment started in 2022 and continued through 2024. The studied group included 34 pregnant and 138 non-pregnant women and they were compared regarding different study variables. Diagnosis of AA was confirmed through clinical examination, ultrasound, diagnostic scoring; Alvarado and Appendicitis Inflammatory Response (AIR) scales in addition to laboratory investigations; white blood cells count and C-reactive protein and the final diagnosis based on the histopathological studies of the excised appendices. Results: The pregnant women contributed for 19.76% of total presented women with AA. Histopathological studies confirmed AA in 161 (93.6%) of cases providing a negative appendectomy rate of 6.4%. Ultrasound showed low sensitivity and specificity rates in pregnant women, 65.6% and 50%, respectively compared to 90.7% and 77.8% in non-pregnant women. Both Alvarado and AIR scoring system showed good diagnostic performance. Pregnant women required longer operation time and longer hospital stay. Complications developed in 8.8% of pregnant and 6.5% of non-pregnant women. No significant differences were found in the complication or readmission rates between pregnant and non-pregnant women. No serious obstetrical complications occurred and no mortalities among the studied group. Conclusions: Open appendectomy for management of pregnant women presented with acute appendicitis is a safe and effective approach during pregnancy. Outcomes of management were not significantly different between pregnant and non-pregnant women. Low negative appendectomy rate of 6.4% and low complication rates of 6.9% were reported among our patients